PROBLEMATIKA KEWENANGAN PENUNTUTAN ANTARA KEJAKSAAN DAN KOMISI PEMBERANTASAN KORUPSI DIKAITKAN DENGAN SISTEM PERADILAN PIDANA - Ginting, Jonta; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Corruption is one of the most fundamental constraints experienced by theIndonesian state. Prosecution of corruption committed by these two institutionsoften make it difficult for law enforcement efforts against corruption. Because it isnot clearly regulated the authority limits both institutions. As well as the unclearposition of the Commission in the Criminal Justice System Indonesia,. Thepurpose of this thesis, namely: First, to know the problems of prosecutorialpowers between the Prosecutor and the Corruption Eradication Commissionassociated with the criminal justice system. Secondly, To know the authority of theCorruption Eradication Commission in the prosecution of corruption associatedwith the criminal justice system. Third, to determine the position Prosecutor andCorruption Eradication Commission in corruption associated with the criminaljustice system.This type of research can be classified into types of normative juridicalresearch, because in this study the authors conducted a study of the legislation onthe subject under study. In this study the source of the data used primary data,secondary data, and the data tertiary data collection techniques in this research isthe study of literature.From this research, there are three main conclusions. First, thereoverlapping authority and conflicts of interest between the Prosecutor and theCorruption Eradication Commission. Secondly, the Corruption EradicationCommission is authorized to prosecute corruption cases. Third, that theProsecutor and the Corruption Eradication Commission has not been clearlyregulated and the position in the Indonesian criminal justice system,Suggestions writer, first, that need to be regulated in the Act regardinglimitation prosecutorial powers between the Prosecutor and the CorruptionEradication Commission. Second, that the eradication of corruption, especially inthe field of prosecution Anticorruption Commission is authorized to conduct theprosecution as stipulated in Law Number 30 of 2002, Three, that needs to beclearly on the positions of the Prosecutor and the Anticorruption commission inthe criminal justice system of Indonesia, so as not to cause a variety of problemsand in the prosecution of corruption.Keywords: Prosecution, Corruption, Prosecutor, Corruption EradicationCommission